Penerapan Metode Visual, Auditory, Kinestethic (Vak) Untuk Meningkatkan Minat Belajar IPA Siswa Kelas IV SD Negeri 02 Tegalgede Tahun 2015/2016 - Hanani, Clara Setyo (2016)
The uses of IPA teaching methods in class IV SDN 02 Tegalgede less varied and cause interest student low. Low interest student on a lesson greatly influence on learning outcomes of the students themselves. To overcome these problems, then applied the learning methods are Visual, Auditory, and Kinesthetic (VAK) in lesson IPA in class IV SD Negeri 02 Tegalgede. The purpose of this study is the application of the method of Visual, Auditory, Kinestethic (VAK) can increase quality of learning, interest and learning outcome IPA fourth grade students of SD Negeri 02 Tegalgede 2015/2016 Academic Year. This type of research is a Classroom Action Research (PTK) used Kurt Lewin model with four stages, namely planning, action, observation, and reflection. The results showed that the students' interest increases, the first conditions of 40, 81%, 66 first cycles, 55%, and the second cycle 81, 98%. Increased interests in learning also have an impact on student learning outcomes. In the first condition of completeness learning are 29 to 41%, the end of the first cycle of 70, 59%, and the end of the second cycle reaches 88, 23%. It can be concluded that by applying the VAK method can increase interest-learning outcomes IPA fourth grade students of SD Negeri 02 Tegalgede 2015/2016 Academic Year.